Time-cost relationships in Australian building construction projects - Love, Peter; Tse, R.; Edwards, D. (American Society of Civil Engineers (ASCE), 2005)
Project time–cost relationships were examined by using project scope factors as predictors for 161 construction projects that were completed in various Australian States using the multiple regression technique of weighted least squares. The analysis was performed between project duration (i.e., time), project type, procurement method, tender type, gross floor area (GFA), and number of stories. An alternative model to that proposed by Bromilow more than three decades ago for forecasting time and cost performance is proposed. It is shown that GFA and the number of stories in a building are key determinants of time performance in projects. Furthermore, the results indicate that cost is a poor predictor of time performance. Limitations and practical implications of the research are also presented.